Enhancement of the electrical conductivity of defective carbon nanotube sheets for organic hybrid thermoelectrics by deposition of Pd nanoparticles. Issue 8 (30th October 2020) - Oshima, Keisuke; Shiraishi, Yukihide; Matsumura, Takuya; Kuriyama, Ayumi; Taguchi, Kazuki; Inoue, Junta; Anno, Hiroaki; Toshima, Naoki
Abstract : Pd nanoparticles can cover the defects of carbon nanotubes by a chemical reduction, which results in an increased carrier transport, then a high thermoelectric figure-of-merit, ZT = 0.3, in the sheets of the defect-repaired carbon nanotubes. Abstract : Although a single carbon nanotube (CNT) has a high thermal conductivity, the randomly assembled sheet has a high potential to be used as an effective thermoelectric (TE) film because of the high electrical conductivity due to the intrinsic property of the CNT and the low thermal conductivity due to phonon scattering at the interfaces of the CNTs. Nevertheless, the high cost of the CNTs limits the practical application of the CNT sheets in TE devices. The recent mass-production of inexpensive CNTs may resolve this problem, although the mass-produced CNTs have many more defects on their surface, which often reduces the electrical conductivity in comparison to the expensive CNTs. We have now discovered that the deposition of palladium nanoparticles (Pd NPs) can enhance the electrical conductivity of the CNT sheets. The electrical conductivity of the mass-produced and defective super-growth CNT (SGCNT) sheets has been found to be increased from about 90 S cm −1 to 170 S cm −1 by depositing the Pd NPs on the SGCNTs by an accumulated chemical reduction method. The results suggested the possibility that the Pd NPs could deposit on the defective sites of the SGCNTs, which produced the improved electrical conductivity of the CNT sheets. Because the SGCNT sheets have a low thermal conductivity, the thermoelectric figure-of-merit ( ZT ) at room temperature was estimated to be as high as ∼0.3.